Utility of Ki-67 and p53 in distinguishing cervical intraepithelial neoplasia 3 from squamous cell carcinoma of the cervix - Tan, Geok Chin; Syed Husain, Sharifah Noor Akmal; Mohd Sidik, Shiran; Shuib, Salwati; Mohd Dali, Ahmad Zailani Hatta; Ng, Paul Hock Oon (Asian Pacific Organization for Cancer Prevention, 2008)
The differentiation between cervical intraepithelial neoplasia 3 (CIN 3) and early squamous cell carcinoma (SCC) of the cervix may be difficult in certain situations. Identification of invasion beyond the basement membrane is the gold standard for the diagnosis of the latter. The objective of this study was to determine whether the use of Ki-67 and p53 could help in solving the above dilemma. This was a retrospective study on 61 cases of cervical neoplasms comprising of 25 cases of CIN 3 and 36 SCC. All cases were evaluated by immunohistochemistry using Ki-67 and p53 monoclonal antibodies. Results showed that the differences of Ki-67 and p53 expression between CIN 3 and SCC were statistically significant. In conclusion, Ki-67 and p53 may serve as helpful adjuncts to routinely-stained histological sections in differentiating between CIN 3 and SCC.